Merdeka Belajar in the Point of View of Learning Technology in the Era of 4.0 and Society 5.0 - Bambang Ismaya; Indra Perdana; Ardian Arifin; Siti Fadjarajani; Samuel PD Anantadjaya; Mas'ud Muhammadiah (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of this article is to describe the autonomous perspective on learning in the Industrial Revolution 4.0 and Society 5.0 eras. This new era provides both benefits and consequences for the eroding of human values. To minimize adverse effects while optimizing its consumption. The point of the study was to define the concept of Merdeka Belajar in the Industrial Revolution 4.0 and Society 5.0 eras. The descriptive-analytic method was combined with a literature review in this investigation. The study's findings highlight a need to strengthen technology's position in the industrial revolution 4.0 in order to foster a more prosperous and civilized human life order, as illustrated in Community Model 5.0. The Indonesian people, in particular, must get familiar with critical educational patterns in order to be prepared to enter the industrial revolution 4.0 and Society 5.0 eras.